THE USE OF TOMATIS METHOD TO IMPROVE STUDENTS’ LISTENING SKILL - Ummi Khaerati Syam (Universitas Muhammadiyah Makassar, 2012)
This research aimed to know the effectiveness of using Tomatis Method to improve the students’ listening skill and to know the student activeness toward teaching-learning process through Tomatis Method of the tenth-grade students of SMK Negeri 2 Makassar. The method of this research consisted of two cycles. One cycle consisted of four meetings. It means that there were eight meetings for two cycles. As a subject in this research was class X in the 2012-2013 academic year with students’ number as about 36 students, 23 of the students are men and 13 students are women. The instruments of this research were observation sheet and listening test or evaluation. The findings of the research were students’ improvement in listening was 64.55 in cycle I and then it became 73.93 in cycle II. The students’ participation in learning the listening process in the first meeting of the cycle I was 59.02% then it became 81.25% in the fourth meeting of cycle II.Keywords: Tomatis Method, Listening, Improve.